Stealing Peanuts and Coercing Energy Drinks: The Underground Economy of a Middle School Summer Camp - Kawecka Nenga, Sandi; Baccam, Tristine P. (Qualitative Sociology Review, 2010)
Economic activities are one important but understudied mechanism which kids use to recreate inequality within their peer cultures. Drawing on ethnographic data from a middle school summer camp, we used Goffman’s typology of economic arrangements to analyze sequences of economic interactions within an underground economy. The middle school students drew on coercion, trading and sharing in order to address their own interests and concerns. When negotiating friendships, girls sometimes engaged in a series of interactions which converted previous social exchanges into unfulfilled economic exchanges. Girls also used inappropriate social exchanges to successfully resist boys’ private coercion efforts, prompting boys to switch tactics and propose appropriate social exchanges and economic exchanges. Not only were these economic interactions patterned along gender, race, and class lines, but the repetitive, routine nature of these interactions helped to recreate inequality within the peer culture.